2013
DOI: 10.1155/2013/827517
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Neural-Derived Peptide Protects the Spinal Cord from Apoptosis after Traumatic Injury

Abstract: Apoptosis is one of the most destructive mechanisms that develop after spinal cord (SC) injury. Immunization with neural-derived peptides (INDPs) such as A91 has shown to reduce the deleterious proinflammatory response and the amount of harmful compounds produced after SC injury. With the notion that the aforementioned elements are apoptotic inducers, we hypothesized that INDPs would reduce apoptosis after SC injury. In order to test this assumption, adult rats were subjected to SC contusion and immunized eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
1
17
0
6
Order By: Relevance
“…Apoptosis is a complex pathophysiological process, mainly completed by the protease cascade mediated by caspase family members, in which caspase-3 serves a key role. Caspase-3 belongs to the cysteine-aspartic protease family that is important in the implementation segment of the apoptosis (31). The present study showed that treatment with geraniol significantly weakened the caspase-3 and caspase-9 activities in SCI rats.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Apoptosis is a complex pathophysiological process, mainly completed by the protease cascade mediated by caspase family members, in which caspase-3 serves a key role. Caspase-3 belongs to the cysteine-aspartic protease family that is important in the implementation segment of the apoptosis (31). The present study showed that treatment with geraniol significantly weakened the caspase-3 and caspase-9 activities in SCI rats.…”
supporting
confidence: 52%
“…Traumatic SCI is a serious and relatively common injury for which there is no clear and effective approach for treatment (31). Following SCI, necrosis and apoptosis occur in nerve cells and tissues.…”
mentioning
confidence: 99%
“…Myelin-derived APLs have been shown to confer beneficial effects in various animal models of autoimmune diseases including EAE (Karin et al, 1994, Tian et al, 2013a, experimental models of spinal cord injury (Rodriguez- Barrera et al, 2013 and peripheral nerve injury (Perera et al, 2015). (Tian et al, 2013a, Gaur et al, 1997, Nicholson et al, 1995, Fischer et al, 2000, Santambrogio et al, 1998, Ruiz et al, 1999, Karin et al, 1994, Brocke et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that many neurons die as a consequence of apoptosis. Therefore, regulating apoptotic cell death might play an important role in the neurological recovery following SCI [99,116]. Recent investigations on the field found that immunizing with A91 decreases caspase-3 activity and TNFα concentrations, reducing the number of apoptotic cells, which is directly correlated with functional improvement after injury [100].…”
Section: The Altered Peptide Ligand A91 As a Potential Treatment For mentioning
confidence: 99%